The Influence of Product Quality and Price Perception on Purchase Decisions of Local Fashion Brand Eiger Product among TikTok Application Users - Najah, Safina; Zawawi, Zawawi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of product quality and price on purchasing decisions for the local fashion brand Eiger on TikTok Shop. The research method used was quantitative with an explanatory approach. The sample consisted of 119 purposively selected respondents. Data were collected through an online questionnaire and analyzed using multiple linear regression. The results showed that product quality and price had a positive and significant effect on purchasing decisions for Eiger products on TikTok Shop, with significance values ​​of 0.004 and 0.000, respectively. The coefficient of determination (R²) of 0.916 indicates that 91.6% of the variation in purchasing decisions is explained by product quality and price, while the remaining 8.4% is influenced by factors outside the research model. These findings confirm that the combination of good product quality and appropriate price is a key factor in increasing consumer purchasing decisions on social media-based e-commerce platforms.